2018
DOI: 10.1002/jobm.201800141
|View full text |Cite
|
Sign up to set email alerts
|

The abundance and mineral‐weathering effectiveness of Bacillus strains in the altered rocks and the soil

Abstract: In this study, we collected different levels of altered rocks of a rocky mountain and the adjacent soil and characterized the abundance and weathering effectiveness of Bacillus strains. Based on qPCR and culture-dependent approaches, the gene copies or the numbers of Bacillus strains were significantly higher in the soil than in the altered rocks, while the ratio of the gene copies or the numbers of Bacillus strains to those of total bacteria was higher in the less altered rock, followed by the more altered ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…The OTU7 sequence was determined to belong to the Bacillus genus and has a 99% similarity with Bacillus cereus. Wang [32] found that many species of the Bacillus genus, including Bacillus cereus, have weathering effects on potassium feldspar and are salt-tolerant. Sofos [36] observed that the growth of Bacillus cereus was completely inhibited when the pH was less than 4.5.…”
Section: Microbial Community Changes At the Genus Levelmentioning
confidence: 99%
“…The OTU7 sequence was determined to belong to the Bacillus genus and has a 99% similarity with Bacillus cereus. Wang [32] found that many species of the Bacillus genus, including Bacillus cereus, have weathering effects on potassium feldspar and are salt-tolerant. Sofos [36] observed that the growth of Bacillus cereus was completely inhibited when the pH was less than 4.5.…”
Section: Microbial Community Changes At the Genus Levelmentioning
confidence: 99%